Pengaruh Kedisiplinan dan Kemandirian Belajar terhadap Prestasi Belajar Siswa pada Mata Pelajaran IPS Kelas IX SMP Negeri 7 Pematang Siantar Tahun Ajaran 2022/2023 - Meilani B.P Manurung; Susy Alestriani Sibagariang; Benjamin Albert Simamora (LP. Ma'arif Janggan Magetan, 2022)
This study aims to determine whether or not there is a significant influence between discipline and independent learning together on student achievement in social studies subject class IX at SMP Negeri 7 Pematang Siantar. The population is all students of class IX with a total of 286 students, and the research sample is 167 students taken using random sampling technique. The data analysis technique uses the analysis prerequisite test, namely normality test and multicollinearity test, and hypothesis testing, namely multiple linear regression test, partial t test, simltan F test, and coefficient of determination test. The results of the study show: (1) there is a significant influence between discipline on student learning achievement, in social studies subjects for class IX at SMP Negeri 7 Pematangsiantar for the Academic Year of 2022/2023. With t arithmetic > t table = 3.416 > 1.654 and a significant value of 0.001 < 0.05. (2) there is a significant influence between learning independence on student achievement in social studies subjects for class IX at SMP Negeri 7 Pematangsiantar for the 2022/2023 academic year. With the value of t arithmetic > t table = 2.020 > 1.654 and a significant value of 0.045 <0.05. (3) there is a significant effect between discipline and learning independence together on student achievement, in social studies subjects for class IX at SMP Negeri 7 Pematangsiantar for the 2022/2023 academic year. With calculated F value > F table = 5.936 > 3.0511 and a significant value of 0.003 < 0.05.